Inhibitory and Toxic Effects of Volatiles Emitted by Strains of Pseudomonas and Serratia on Growth and Survival of Selected Microorganisms, Caenorhabditis elegans, and Drosophila melanogaster. (11th June 2014) - Popova, Alexandra A.; Koksharova, Olga A.; Lipasova, Valentina A.; Zaitseva, Julia V.; Katkova-Zhukotskaya, Olga A.; Eremina, Svetlana Iu.; Mironov, Alexander S.; Chernin, Leonid S.; Khmel, Inessa A.
Abstract : In previous research, volatile organic compounds (VOCs) emitted by various bacteria into the chemosphere were suggested to play a significant role in the antagonistic interactions between microorganisms occupying the same ecological niche and between bacteria and target eukaryotes. Moreover, a number of volatiles released by bacteria were reported to suppress quorum-sensing cell-to-cell communication in bacteria, and to stimulate plant growth. Here, volatiles produced by Pseudomonas and Serratia strains isolated mainly from the soil or rhizosphere exhibited bacteriostatic action on phytopathogenic Agrobacterium tumefaciens and fungi and demonstrated a killing effect on cyanobacteria, flies ( Drosophila melanogaster ), and nematodes ( Caenorhabditis elegans ). VOCs emitted by the rhizospheric Pseudomonas chlororaphis strain 449 and by Serratia proteamaculans strain 94 isolated from spoiled meat were identified using gas chromatography-mass spectrometry analysis, and the effects of the main headspace compounds—ketones (2-nonanone, 2-heptanone, 2-undecanone) and dimethyl disulfide—were inhibitory toward the tested microorganisms, nematodes, and flies. The data confirmed the role of bacterial volatiles as important compounds involved in interactions between organisms under natural ecological conditions.